PERFORMANCE ANALYSIS OF RDE ENERGY CONVERSION SYSTEM IN VARIOUS REACTOR POWER CONDITION - Ignatius Djoko Irianto; Sukmanto Dibyo; Sriyono Sriyono; Djati H Salimy; Rahayu Kusumastuti; Marliyadi Pancoko (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Reaktor Daya Eksperimental (RDE) is an experimental power reactor based on High Temperature Gas-cooled Reactor (HTGR) technology with thermal power of 10 MW. As an experimental power reactor, RDE is designed for electricity generation and provides thermal energy for experimental purposes. RDE energy conversion system is designed with cogeneration configuration in the Rankine cycle. To ensure the effectiveness of its cogeneration, the outlet temperature of the RDE is set at 700°C and steam generator outlet temperature is around 530°C. Analysis of the performance of the energy conversion system in various power levels is needed to determine the RDE operating conditions. This research is aimed to study the performance characteristics of RDE energy conversion systems in various reactor power conditions. The analysis was carried out by simulating thermodynamic parameter calculations on the RDE energy conversion system and the overall cooling system using the ChemCad program package. The simulation is carried out by increasing the reactor power from 0 MW to 10 MW at constant pressure and constant mass flow rate. The simulation results show that the steam fraction at the steam generator outlet increases starting from 3 MW reactor power and reaches saturated steam after the thermal power level of 7.5 MW. From the results, it can be concluded that with constant mass flow rate and operating pressure, optimal turbine power is obtained after the reactor thermal power reached 7.5 MW.Keywords: RDE, Energy Conversion System, Performance, Reactor Power, ChemCad